Surimi Modifikasi pH Pencucian Daging Ikan Tongkol (Euthynnus sp) Terhadap Karakteristik Surimi Yang Dihasilkan - Laksono, Untung Trimo; Putra, Endo Pebri Dani; Kusumawati, Rr. Puji Hastuti; Lasmi, Leni; Kartini, Sitta Indah (Jurnal Kelautan, Lingkungan, dan Perikanan, 2024)
The use of fish high in sarcoplasm such as tongkol (Euthynnus sp) as raw material for surimi requires a washing process to increase the yield and level of gel strength. Modifying the pH of washing surimi to be more alkaline is an effective method for increasing protein yield in the surimi processing. The aim of this research is to obtain the optimal surimi protein yield and determine the characteristics of the resulting gel. The research results showed that the optimum pH for washing tongkol surimi was pH 8 with 2 times washing (p>01). The proximate values ​​of tongkol are 76.58% water, 18.23% protein, 2.34% fat, 1.22% ash and 1.63% carbohydrates (By different). The proportion of sarcoplasmic protein and myofibrils in tongkol meat is 49.0% and 45.90%. The highest yield was obtained when modifying the water pH to 8 and twice washing time is about 64.75%. The texture characteristics of the kamaboko surimi profile analyzer were modified with washing water pH 8 and twice washing time, hardness 300 g, gumminess 202.90 g and chewiness 98.97 mJ. The water holding capacity (WHC) of kamaboko surimi tongkol is 53.50%.